EDUKASI CARA MEMAKAI, MELEPAS, MEMBUANG MASKER SEKALI PAKAI DAN PENJELASAN PENTINGNYA VAKSIN COVID-19 PADA ANAK SD - Nurul Fatwati Fitriana; Jumiati Riskiyani Dwi Nandia; Atika Dhiah Anggraeni; Suci Ratna Estria; Abdul Hakim Nitiprojo; Destiya Dwi P (COVIT (Community Service of Health), 2022)
Since March 2020, Indonesian has become one of  the countries on the list of the spread of the Covid-19 virus pandemic. This has an impact on the education sector. Elementary school age children are one of the age groups that are vulnerable to the Covid-19 virus and Indonesia in of the countries with the highest child Covid-19 death rate in the world. The year 2022 is known as the normal area. The Ministry of Education and Culture gives regional authority to hold limited face-to-face meetings while continuing to carry out health protocols. One of health protocols implemented is wearing a mask. Health education that is often done is wearing the right mask, but for education what do and don’t while wearing mask, removing the mask and disposing of the mask properly is still rarely done. The use of masks and proper treatment of mask contribute to breaking the chain of the spread of the Covid-19 Virus. This activity aims to provide education on the importance of mask management, mask removal, and mask disposal. The method used is counseling and joint simulation. Students who take part in the activity give a good response by paying attention and participating in the activity.   Keyword : COVID-19, Mask, Vaccine